Widows & orphans eaudiobook - Meissner, Susan (christianaudio, 2016)
When attorney Rachael Flynn learns her bighearted younger brother has been arrested, she at first takes it in stride; Joshua has been in trouble before when his zeal for helping the downtrodden and disadvantaged pitted him against the law. But this time the charge is murder and he's confessed to the crime. Certain that he's innocent, Rachael begs Joshua to let her represent him, but her brother refuses her offer of counsel. As Rachael works on the case on her own, she begins to suspect that Josh knows who the real killer is, but she's unable to get him to cooperate with his defense. When Rachael asks her husband, Trace, and his fellow artist friends to sketch the scene of the crime as they see it, a new piece of the puzzle becomes apparent...a piece that ultimately leads to a much bigger truth. "A powerful story of family and faith, wrapped in a mystery that touches the deep corners of the heart. Susan Meissner writes with a sure hand, and this book will make her many new fans." —James Scott Bell, bestselling author of Presumed Guilty